The Validation of Office Administration for Teachers at MTs Al Watoniyah Bojong Village through the Use of Digital Signatures and Online Forums - Budiman, Adam Arif; Setiawan, Aji; Susilo, Andi (Fakultas Teknik Universitas Darma Persada, 2024)
Using digital signature apps and communication platforms such as Discord has become essential in supporting teachers' administrative work in the digital era. Digital signature apps allow teachers to sign documents quickly, securely, and legally without meeting face-to-face. This speeds up the approval process of documents such as report cards, decision letters, and other administrative forms, thereby increasing efficiency and reducing reliance on physical documents. Initially developed for the gaming community, Discord has become an effective communication platform in educational settings. Features like voice chat, video calls, and discussion channel settings allow teachers to collaborate with colleagues, hold online meetings, and manage classes virtually. Their integration supports teacher productivity in daily administrative tasks, especially in remote work. Applying these technologies strengthens teachers' digital literacy skills, reduces their administrative burden, and allows them to focus more on developing the teaching-learning process. Thus, using digital signature apps and Discord is an essential part of digital transformation in the increasingly dynamic world of education.